Repercussões contemporâneas do paradoxo do mentiroso: Tarski e Kripke - Guilherme Araujo Cardoso (2010)
The purpose of this dissertation is to discuss the problems raised by the Liar Paradox in general. We are going to present and compare the two main ways of solution to this paradox: The Orthodox Solution and the Alternative Solution. Both of them start from Tarskis diagnosis. According to this diagnosis the paradox is a consequence of two essential features: The semantically closed languages and the preservation of classical logic. The Orthodox Solution keeps classical logic but it has to open the semantic of the language. The Alternative Solution keeps the language semantically closed even if it implies some kind of restriction on classical logic. We will try to show that from both these sides what we have are just results that can, at most, be thought as partially satisfactory. We will show a general picture of the solutions, but mainly considering Tarski and Kripkes theories.